Recent translational research: antiangiogenic therapy for breast cancer – where do we stand? - Miller, Kathy D (BioMed Central, 2004)
The central importance of angiogenesis and our understanding of how new blood vessels are formed have led to the development of novel antiangiogenic therapies. Although the number of agents in development has grown exponentially, only one phase III trial in breast cancer has been completed. In that study the addition of bevacizumab to capecitabine did not extend the progression-free survival of patients with refractory disease as compared with capecitabine monotherapy. Early enthusiasm for antiangiogenic therapy must give way to clinical reality. Our challenge now is to exploit better the activity of antiangiogenic agents seen in the early clinical studies.